Anestezjologia i intensywna terapia Heparin induced thrombocytopenia as a complication of coronary artery by-pass surgery – case report - Kucewicz-Czech, Ewa; Kaczmarski, Jacek; Podwińska, Ewa; Wojarski, Jacek; Pakosiewicz, Waldemar; Przybylski, Marcin; Knapik, Piotr; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
A 67-year-old woman with ischemic cardiomyopathy (EF=32%) was scheduled for elective coronary artery by-pass grafting surgery. The operation was performed on the beating heart (OPCAB). In the early postoperative period the syndrome of low cardiac output was diagnosed and intraaortic pump was inserted. The continuous infusion of unfractionated heparin was started. In a few postoperative days improvement in cardiac function was observed and intraaortic counterpulsation was terminated. Simultaneously the infusion of heparin was stopped and low molecular weight heparin was applied. On the 10th postoperative day an unexpected fall in platelet count was observed. Clinical signs of thrombosis were not present. The low molecular weight heparin treatment was discontinued and warfarin introduced. INR was kept below 3. The results of laboratory tests for heparin – induced thrombocytopenia antibodies were positive. After several days of treatment the platelet count returned within the normal range. Patients undergoing cardiac surgery are at risk of HIT. The reported incidence of postoperative antibody seroconversion in cardiac surgery patients ranges between 25-50%. The risk of developing clinical HIT is influenced by the heparin treatment.